Brain metabolic changes in patients with treatment resistant schizophrenia treated with deep brain stimulation: A series of cases. (August 2020) - Roldán, Alexandra; Portella, Maria J.; Sampedro, Frederic; Alonso-Solís, Anna; Sarró, Salvador; Rabella, Mireia; Grasa, Eva M.; Álvarez, Enric; Rodríguez, Rodrigo; Camacho, Valle; Fernandez-León, Alejandro; Fuentes, Francisco; et al.
Abstract: Deep brain stimulation (DBS) has been found to be effective in treatment resistant neurological and psychiatric disorders. So far there has been only one completed trial in schizophrenia, in which seven treatment resistant patients received DBS in the subgenual anterior cingulate cortex (sgACC, N = 4) or the nucleus accumbens (NAc, N = 3); four met symptomatic response criteria over the trial period. Six patients underwent 18 F-FDG PET at baseline and after at least 6 months of stimulation. Individual patient analysis indicated that DBS to both the sgACC and NAc was associated with local and distant changes in glucose metabolism. Increments and decrements of brain activity were observed in regions that included the medial prefrontal cortex, the dorsolateral prefrontal cortex, the anterior cingulate cortex, the caudate nucleus, the NAc, the hippocampus and the thalamus. Increased activity appeared to be associated with clinical improvement. These preliminary findings suggest that DBS acts by modulating cerebral activity in the cortico-basal-thalamic-cortical circuit in patients with schizophrenia who show improvement in psychotic symptoms.